Examination of the influence of treatments and mineral composition on the point of zero charge of red mud - Aleksandar Došić; Gordana Ostojić (Zaštita Materijala)
Red mud represents tailings which remains after the processing of bauxite into alumina by Bayer's proceedings. All the elements are present in the red mud are found in the form of different minerals. These minerals do not exist as individual particles, but are associated with other minerals in aggregates which represent particles of red mud. Surface charge is an important property of the red mud, which affects a number of its characteristics. Surface charge can be considered through the zero charge point. In this paper, the point of zero charge of the original red mud and certain treated samples is determined. Incomplete washing, thermal and acid treatment were used as treatments. The applied treatments had a different effect on the movement of the PZC and buffer region. The red mud sample was distinguished by a high value of pHPZC (9.7 ± 0.2). Incomplete washing did not affect the change in PZC, while thoroughly rinsing caused a significant movement of PZC to a lower pH. This suggests to a large amount of residual base from the leaching process. Thermal treatment of red mud did not significantly affect the change in the final pH at which plateau was observed (pHPZC 9.4-9.9), while acid treatment had a more pronounced effect (pHPZC 6.2-7.9). PZC values for acid-treated samples obtained in an inert electrolyte were lower than those obtained in distilled water, at least for one pH unit. All the analysed samples had a pronounced buffer region in which the final pH values were independent of the initial ones. Partial rinsing and thermal treatment did not significantly affect the change in buffer region, while acid treatment caused the narrowing of the buffer region with increasing acid concentration, but the samples continued to retain significant neutralization capacity. For the move of the PZC treated muds, major responsibility have phase changes that occur in the treatment, neutralization of the residual base and the anions in the solution, and changing the crystallinity and the solubility of minerals in the mud. Applying the appropriate treatment can affect the change in the mineral composition and, consequently, the changes in the charge of the surface.